Heart and pulmonary artery remodeling association with various levels of natriuretic peptides and renin-angiotensin-aldosterone system activation in patients with pulmonary hypertension of various etiology - Yu. A. Andreeva; M. A. Saidova; T. V. Martynyuk; V. P. Masenko; S. N. Nakonechnikov; I. E. Chazova (Кардиоваскулярная терапия и профилактика)
Aim. To study the associations between heart and pulmonary artery (PA) remodeling severity, according to echocardiography data, natriuretic peptide (NUP) levels, and renin-angiotensin-aldosterone system (RAAS) activation among patients with pulmonary hypertension (PH) of various etiology.Material and methods. The study involved 111 patients with PH, including 30 subjects with idiopathic PH (IPH), 16with chronic PA thromboembolia (PATE), 19 with systemic scleroderma (SS), 15 with chronic obstructive pulmonary disease (COPD), 18 with congenital heart disease (CHD), 13 with residual PH (RPH), as well as 21 healthy controls. In all participants, echocardiography, EchoCG (Vivid 7, GE, USA) and measurement of plasma brain and atrial NUP, angiotensin II (AT II) and plasma renin activity (PRA) were performed.Results. Significant increase in NUP levels was observed in all subgroups, especially in those with PATE and IPH. RAAS activation was detected in all subgroups excluding those with COPD, being maximal in SS subgroup. In all subgroups, dilatation of right heart chambers and PA trunk, as well as decrease in right ventricular (RV) ejection fraction (EF), was observed. Heart remodeling severity was maximal in subjects with IPH, CHD, and PATE, and minimal - in those with SS and COPD, which is consistent with PA systolic pressure and RVEF levels in respective subgroups.Conclusion. Heart remodeling was observed in all PH patients, being maximal in IPH, CHD, and PATE subgroups. Elevated NUP level, registered in all PH subjects, was highest in PATE and IPH subgroups. Significantly increased levels of PRA and AT II were observed in SS, IPH, and PATE individuals, with maximal RAAS activation among SS patients.